Visualization display and exit fault diagnosis of secondary virtual real circuit in intelligent substation - Wang, Zhufeng; Kong, Fanfang; Chen, Peixun; Tu, Deran; Chen, Qinghui (Electric power systems research, 2024)
•Based on the characteristics of hierarchical query and radial traversal using breadth first search algorithm, a virtual real mapping scheme for intelligent substation fiber optic circuit is proposed. The breadth first search algorithm is used to traverse and visualize the fiber optic circuit. The fault area is divided according to the mapping relationship between the virtual and real circuits, and D-S evidence theory is used for accurate fault location. The fault type is identified using multi-source information such as device port status and virtual circuit fault characteristics through the evidence table method.•This article utilizes the advantage of intelligent substations providing massive information to enhance the control ability of operation and maintenance personnel over secondary equipment and fiber optic circuits, promoting the development of intelligent substation secondary equipment operation and maintenance.•This scheme promotes the healthy development of intelligent substations and meets the emerging application demands in secondary equipment operation and maintenance.•The fiber optic loop virtual real mapping scheme will provide rich data resources for intelligent substations. Most communication in smart substations uses fiber optic connections to connect secondary equipment now. Due to the lack of intuitive connection between devices, it leads to difficulties in monitoring and relay protection. In order to solve the problems of visualizing, monitoring, and diagnosing secondary virtual circuits in the operation and maintenance of intelligent substations, a comprehensive monitoring technology system for secondary virtual circuits in intelligent substations is constructed. Firstly, a breadth first search algorithm is proposed to sort out the physical connection relationships between secondary devices, which achieves visual display of secondary virtual circuits. Then, based on deep search fault inference algorithms, it can diagnose and locate the fault area. Through the massive data source of intelligent substations, multiple information fusion can be achieved. By applying the D-S evidence theory, precise fault localization can be achieved. Finally, the proof table method is used to determine the type of fault and to meet the practical application requirements for the operation and maintenance of secondary equipment in intelligent substations.